Remember Gerhard Richter in the Thunderstorm of Beethoven: The Influence of Cross-Sensory Coupling on Memory, Intercultural Communication, and the Verbalization of Paintings and Sounds - Martinez, Emilie (Research in Language, 2013)
This interdisciplinary study focuses on the perception and verbalization of messages conveyed through instrumental music, soundscapes, and contemporary paintings. International young-adult university students learning German participated in a series of experiments conducted at Friedrich Schiller University in Jena, Germany. To incorporate globalization and cultural difference into this analysis, the author compared the reactions of Western and Asian participants to auditory and visual stimuli. This paper explores the concepts of mixed media, cross-sensory coupling, and esthetic synesthesia, and throws new light on the contribution of cross-sensory coupling to verbalization and to long-term memory processes, from encoding to retrieval. In addition, the author demonstrates how intercultural communication is based upon universal emotions aroused by contemporary paintings, instrumental music and soundscapes.